Pendampingan Siswa yang Berkesulitan Belajar Matematika di Kelas VII SMP Negeri 15 Kerinci - Melsita, Holdia; Putri, Rani Manisa; Juliani, Rezki Putri; Putra, Aan (ABJIS: Al-Bahjah Journal of Islamic Community Service, 2025)
Students who have obstacles in learning mathematics often have difficulty in solving problems due to deficiency of concepts understanding, afraid of making mistakes and receiving revisions from teachers, and initially assume that mathematics is difficult. Mentoring was carried out in class VII of SMP Negeri 15 Kerinci on the material of One Variable Linear Equations. The mentoring team consisted of 3 mentors who were carried out at school and outside of school. The mentors provided assistance by re-explaining the material and parts that were difficult for students to understand and also helping students in doing assignments given by the teacher. With this mentoring, the difficulties experienced by students in learning mathematics can be reduced and students can understand the material clearly. As a result of the mentoring, students who had difficulty in addition, subtraction, multiplication, division and lacked understanding of reading questions and also students who did not like mathematics lessons were helped in understanding the material being taught. The mentoring team received a very good response from students and teachers, with the presence of the mentoring team students were willing to work on the questions given and learn to solve the questions